THE INFLUENCE OF CONTENT MARKETING, LIVE STREAMING, AND ONLINE CUSTOMER REVIEWS ON PURCHASE DECISIONS AT TIKTOK SHOP - Aprilya, Arintha Galuh; Indayani, Lilik; Hariasih, Misti (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
Currently, a new term has emerged for this type of e-commerce, namely social commerce. TikTok Shop is a social commerce application that people like. Consumers can use the features available on the TikTok Shop, such as uploading content, live streaming, and customer reviews. These features can help consumers in determining purchasing decisions for a product. The aim of this research is to determine the influence of content marketing, live streaming, and online customer reviews on purchasing decisions. This research used quantitative methods with a total of 96 respondents. The data source in this research consists of primary data in the form of questionnaires distributed to respondents. Meanwhile, secondary data comes from journal articles, books and websites. Data collection was obtained through Google Form and Likert scale. SPSS software is used. Tests include descriptive analysis test, multi collinearity test, heteros cedasticity test, autocorrelate, T and F test, and R2 coefficient determination. The research results showed that the variables content marketing, live streaming, and inline customer reviews has a positive significant effects on purchasing decision variables.